Collisions of water droplets in the high-temperature air. (May 2021) - Tkachenko, P.P.; Shlegel, N.E.; Strizhak, P.A.
Highlights: Characteristics of water droplet collisions in air heated to 700 о С were established. The higher the air temperature, the faster the surface of droplets transforms. Transition boundaries on collision regime maps change significantly at higher heating temperatures. High-temperature heating of gas medium results in two bounce areas on droplet interaction regime maps. The higher temperature, the fewer child droplets are formed in disruption for Weber number below 100. Abstract: The paper presents experimental research findings on the integral characteristics of the interaction of water droplets in a gas heated to high temperatures. An induction heater with an internal volume of about 0.13 m 3 was used. It was fitted with quartz glass observation windows to record the characteristics of droplet motion before and after collisions. Air was used as a gas medium in the inductor. The parameters were varied in the following ranges: the air medium temperature 20–700 °С, the initial radius of droplets 0.3–0.9 mm, their velocity 0.1–7 m/s and impact angle 0–90°. At high gas temperatures, droplets were two-phase objects, because vapor bubbles formed in their near-surface layer. Frames with four collision regimes (coalescence, separation, disruption and bounce) were recorded. There were significant differences in the transformation of the water droplet surface and in the interaction of droplets with each other at various gas temperatures in the heating chamber. It has been shown that the growth of the air temperature increases the droplet lifetime and causes them to deviate from the spherical shape. The effect of the gas temperature on the position of droplet collision boundaries was determined with due consideration of the relative linear interaction parameter and the Weber number. When the gas temperature increases, two areas may form, corresponding to the bounce of droplets on the collision regime map. Differences were established in the number and dimensions of secondary water droplets formed from the collision of two initial ones. The total surface areas of liquid before and after droplet collisions were calculated. Graphical abstract: Image, graphical abstract